2014
DOI: 10.1073/pnas.1317395111
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the antagonism of retinoblastoma protein dephosphorylation by PNUTS provides insights into the PP1 regulatory code

Abstract: The serine/threonine protein phosphatase 1 (PP1) dephosphorylates hundreds of key biological targets by associating with nearly 200 regulatory proteins to form highly specific holoenzymes. However, how these proteins direct PP1 specificity and the ability to predict how these PP1 interacting proteins bind PP1 from sequence alone is still missing. PP1 nuclear targeting subunit (PNUTS) is a PP1 targeting protein that, with PP1, plays a central role in the nucleus, where it regulates chromatin decondensation, RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
188
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(202 citation statements)
references
References 36 publications
7
188
0
Order By: Relevance
“…2D). The K d of GADD34 552-567 for PP1 was ~6.5-fold weaker than that determined for some PP1 regulators, namely PNUTS and spinophilin (Choy et al, 2014; Ragusa et al, 2010) (8.7 nM and 9.3 nM, respectively), but close to that for NIPP1 (K d of 73 nM) (O’Connell et al, 2012). Competitive fluorescence anisotropy experiments with a longer GADD34 construct confirmed that GADD34 552-567 constitutes the complete PP1 binding domain (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…2D). The K d of GADD34 552-567 for PP1 was ~6.5-fold weaker than that determined for some PP1 regulators, namely PNUTS and spinophilin (Choy et al, 2014; Ragusa et al, 2010) (8.7 nM and 9.3 nM, respectively), but close to that for NIPP1 (K d of 73 nM) (O’Connell et al, 2012). Competitive fluorescence anisotropy experiments with a longer GADD34 construct confirmed that GADD34 552-567 constitutes the complete PP1 binding domain (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…[FW]. NCX1 sequences were also screened for the presence of the ⌽ 1 ⌽ 2 and/or arginine motifs, as defined by Choy et al (36). Lasergene (DNA Star, Madison, WI) was used for protein alignments.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in addition to the RVXF PP1-binding motif, the partial ⌽ 1 ⌽ 2 motif and the conserved Arg-428 on NCX1 may form part of a high affinity PP1-binding site. The Arg motif in the PP1 nuclear targeting subunit (PNUTS)-PP1 holoenzyme has been shown to work as a substrate selectivity filter, by blocking access to the C-terminal binding groove (36). Therefore, dephosphorylation of pSer-68-PLM may not require binding to the C-terminal groove, and PP1 interaction sites such as SILK (55) and MyPhoNE (56) were not found in NCX1.…”
Section: Pp1c Anchors To the Ncx1-kiff/kvff Motif In Cbd1-pp1mentioning
confidence: 99%
“…We investigated this question through a preliminary NMR study. The 1 H, 15 N Heteronuclear Single Quantum Coherence (HSQC) spectrum of 15 N-labelled PNUTS showed high dispersion of well-defined backbone NH resonances with uniform intensity of the signals (Fig 4).…”
Section: The N-terminal Domain Of Pnuts Adopts a Globular Foldmentioning
confidence: 99%
“…The PNUTS C-terminal region contains a zinc finger domain implying a possible interaction with nucleic acids [14], although this domain in PNUTS is not known to bind either RNA or DNA. The polypeptide region between the TFIIS LW and zinc finger domains in PNUTS is highly unstructured and plays a conserved role in binding to PP1 [15][16][17].…”
Section: Introductionmentioning
confidence: 99%